Personal values and gift giving act: a proposed connection (2020)
The consumption of gifts is relevant and many commerce sales are carried out during traditional times of gift-giving, such as Christmas. The objective of this paper is to propose and validate a model that measures the influence of personal values in the act of gift giving, also considering the role of gender in these relationships. A survey was carried out on 1,085 consumers. Through structural equation modeling with partial least squares (SEM-PLS), it was verified that the gift giving act is influenced by five personal values: self-direction, hedonism, tradition, achievement, and power. The results show that personal values can be used to predict the behavior of gifting. This study integrates Gift-Giving Theory and Personal Values Theory to better understand consumer attitudes and behaviors.